الرمز الصوفي : دراسة تأويلية - Samihah Nesraoui (Hasanuddin University, 2016)
The mystic adapted a way of expressing what is inside him, for this , his sense become deep with eloquent purposes and emotional experience stemming from the spirit world and the subconscious in which his spirit wander . what made the expressions characterized by ambiguity and hiding behind the symbol, this is what demand the using of reader’s minds to try uncovering the facts that lie behind this mystical language which contains a lot of shapes indicative of semiotics that require interpretation , thus field remains open to other readings and extract a new mystical truth . From symbols used by poets mysticism, feminine symbol, symbol of wine and a symbol of nature , in which the poet expresses about a Godly love .therefore we tried through this article stand on the connotations of these symbols in the poetry of some poets mysticism the Mamluk era, and try to pur interpretations to it, and devise meanings of their mystical love.